"I was stabbed in the head 11 days ago". Issue 8 (25th July 2008) - Chalkley, D; Huseyin, T; Jacobs, P
Abstract : A case is presented in which a knife wound to the head was initially assessed as inconsequential and later proved to be significant. This case illustrates the necessity of exploring scalp wounds to assess for possible skull fractures and of using the history to direct management. It also highlights the requirement for thorough guidelines for use by junior staff and for the staff to apply them with some degree of latitude.